Glucocorticoids Decrease Longitudinal Bone Growth in Pediatric Kidney Transplant Recipients by Stimulating the FGF23/FGFR3 Signaling Pathway. (26th August 2019) - Delucchi, Ángela; Toro, Luis; Alzamora, Rodrigo; Barrientos, Victor; González, Magdalena; Andaur, Rodrigo; León, Pablo; Villanueva, Francisco; Galindo, Mario; Las Heras, Facundo; Montecino, Martín; Moena, Daniel; et al.
ABSTRACT: Renal transplantation (RTx) is an effective therapy to improve clinical outcomes in pediatric patients with terminal chronic kidney disease. However, chronic immunosuppression with glucocorticoids (GCs) reduces bone growth and BMD. The mechanisms causing GC‐induced growth impairment have not been fully clarified. Fibroblast growth factor 23 (FGF23) is a peptide hormone that regulates phosphate homeostasis and bone growth. In pathological conditions, FGF23 excess or abnormal FGF receptors (FGFR) activity leads to bone growth impairment. Experimental data indicate that FGF23 expression is induced by chronic GC exposure. Therefore, we hypothesize that GCs impair bone growth by increasing FGF23 expression, which has direct effects on bone growth plate. In a post hoc analysis of a multicentric randomized clinical trial of prepubertal RTx children treated with early GC withdrawal or chronic GC treatment, we observed that GC withdrawal was associated with improvement in longitudinal growth and BMD, and lower plasma FGF23 levels as compared with a chronic GC group. In prepubertal rats, GC‐induced bone growth retardation correlated with increased plasma FGF23 and bone FGF23 expression. Additionally, GC treatment decreased FGFR1 expression whereas it increased FGFR3 expression in mouse tibia explants. The GC‐induced bone growth impairment in tibiae explants was prevented by blockade of FGF23 receptors using either a pan‐FGFR antagonist (PD173074), a C‐terminal FGF23 peptide (FGF23180‐205) which blocks the binding of FGF23 to the FGFR‐Klotho complex or a specific FGFR3 antagonist (P3). Finally, local administration of PD173074 into the tibia growth plate ameliorated cartilage growth impairment in GC‐treated rats. These results show that GC treatment partially reduces longitudinal bone growth via upregulation of FGF23 and FGFR3 expression, thus suggesting that the FGF23/Klotho/FGFR3 axis at the growth plate could be a potential therapeutic target for the management of GC‐induced growth impairment in children.